Phenotypic and Genotypic Characterization of ESBL Bacteria in the Human Population - Raza, Zahra; Ali, Naeem; Ali, Shaukat; Raza, Muhammad Naeem; Azad, Ayesha (Journal of Agriculture and Biology, 2025)
Growing occurrence of antimicrobial resistance (AMR) in humans has become an intense global concern. Dissemination of extended-spectrum beta- lactamase (ESBL) producing Escherichia coli across the geographic boundaries is causing a grave challenge to the efficacy of antimicrobial agents. The purpose of this work is to demonstrate the mechanism of antibiotic resistance patterns prevailing in human interface and the need to employ one health approach to counter these alarming trends. Our objective was to inspect the MDR (Multi Drug Resistant) Enterobacter isolates for specific ESBL producing genes (CTX-M, SHV, TEM and OXA) and elicit the resistance profiling of Enterobacteriaceae family using conventional PCR. The study also intended to establish a One Health link in the dissemination and incidence patterns of ESBL bacteria. Bacterial strains were isolated by employing Gene JET Gel genomic kit. After isolation of bacterial DNA and gel electrophoresis clear DNA bands in the 1% agarose gel were obtained. Out of 100 isolates, 31 (31%) isolates were ESBL producers showing a greater degree of resistance to antibiotics. Its prevalence is not common in humans. Highest level of resistance was found in Amoxicillin followed by Ceftriaxone. Elements of resistance were also found in TZP, NIT and CTX in varying degrees. The resistance pattern in the samples taken from human were almost the same with minute differences. This indicates that a common resistance mechanism is operating across these different sources, while also highlighting multiple pathways through which humans are exposed to resistant bacteria and their associated resistance genes. Future work in this area will need enhanced statistical capabilities and multiple samples from humans. Techniques of molecular biology like meta-genomic analysis of entire DNA, and bioinformatics analytical tools have the potential to replace current techniques.
Keywords: Antimicrobial resistance; ESBL; Multidrug resistance; Enterobacteriaceae; Human interface